Letter (copy) : Help for the Workers of Spain Fund - Tewson, Vincent
028-0180-001 Our Ref: HVT/FC/EK/57. 24th September, 1936. Mr. D. Goldstick, National Council Canadian League Against War and Fascism, 73, Adelaide Street, West, Toronto, Ontario. Dear Mr. Goldstick, HELP FOR THE WORKERS OF SPAIN FUND. Many thanks for your letter of the 31st ultimo enclosing a donation of eighty dollars for the above fund. I have pleasure in enclosing herewith our receipt for this amount made out in favour of the Spanish Cigar Makers' Union. It is very encouraging to know the volume of support which there is in Canada and the U.S.A. for the International Fund which has been set up by the International Federation of Trade Unions and the L.S.I. It may be of interest and assistance for you to know that large supplies of food, tobacco and medicaments (including over £4,000 worth of anti-tetanus serum) have been sent to Spain and the fund is being administered by a Joint Committee of the two Internationals in the closest touch with our colleagues in Spain. Referring to your request for literature I am enclosing copy of a leaflet which we have published and a report of the debate which took place at our Plymouth Congress at the beginning of this month on the Spanish situation. Yours sincerely, for Joint Secretary. Receipt. Leafelt. Report. 292/946/28/180